The Orientation and Implications of New Criminal Code: An Analysis of Lawrence Friedman's Legal System - Flora, Henny Saida; Thuong, Mac Thi Hoai; Erawati, Ratna Deliana (Magister of Law, Faculty of Law, University of Mataram, 2023)
This study aims to analyze the orientation and implications of the legalization of the Draft Criminal Code (RKUHP) to become Law No. 1 of 2023 concerning the Criminal Code (New Criminal Code) regarding the legal system theory of Lawrence M. Friedman. This research is normative legal research by prioritizing conceptual and statutory approaches. The results of the study confirm that the orientation of Lawrence Friedman’s legal system regarding the ratification of the Draft Criminal Code is that the aspects of legal substance in the New Criminal Code have adopted Indonesian legal values and culture by applying the concept of restorative justice. From the aspect of legal structure, implementing the New Criminal Code in a transitional manner for three years has an orientation to provide socialization. From the aspect of legal culture, the orientation of restorative justice involves the public in the criminal justice process. The implication of Lawrence Friedman’s legal system puts forward the substance of customary law as the applicable law, related to the idea of restorative justice to the affirmation that imprisonment is a last resort. That has implications for the need for judges to understand customary law. From the aspect of the legal structure, the roles of judges, prosecutors and other law enforcement officials are also prioritized to provide the essence of justice in implementing the New Criminal Code. From the aspect of legal culture, the role and participation of the community are essential in efforts to prevent and enforce criminal law in society.